Electrochemistry of phenol in bis{(trifluoromethyl)sulfonyl}amide ([NTf2](-)) based ionic liquids - Villagran, C; Aldous, L; Lagunas, M; Compton, R; Hardacre, C (2006)
The electrochemistry of phenol and 4-tert-butyl-phenol is described in [C2mim][NTf2] and [C4mpyrr][NTf2] ionic liquids. Oxidation of phenol and phenolate is observed at Epa=+1.64and+0.24V vs. Ag in both ionic liquids. On the cathodic sweep at a potential of -2.05 V vs. Ag under an oxygen atmosphere, the production of O22- dianions triggers the formation of phenolate anions which undergo chemical oxidation to the phenoxyl radical. The phenoxyl radical then reacts with the [NTf2]- anion of the ionic liquid to form the corresponding phenyl triflate molecule. © 2005 Elsevier B.V. All rights reserved.